A novel solid–gas thermochemical multilevel sorption thermal battery for cascaded solar thermal energy storage. (1st January 2016) - Li, T.X.; Wu, S.; Yan, T.; Xu, J.X.; Wang, R.Z.
Graphical abstract: Solid–gas thermochemical multilevel sorption thermal battery for cascaded thermal energy storage. Highlights: A novel solid–gas thermochemical multilevel sorption thermal battery for energy storage. Cascaded solar heat storage using thermochemical multilevel sorption thermal battery. Performance of the thermochemical multilevel sorption thermal battery is analyzed. The proposed method has high energy density and broad working temperature range. Energy density of the proposed method is sensitive to chemical global conversion. Abstract: An innovative solid–gas thermochemical multilevel sorption thermal battery is developed for cascaded solar thermal energy storage to enhance the versatility and working reliability of solar heat storage system by widening the working temperature range. Solar thermal energy can be stored in the form of bond energy of sorption potential at different cascaded temperatures resulting from solid–gas thermochemical multilevel sorption processes. The operating principle and working performance of the thermochemical multilevel sorption thermal battery for energy storage is described and analyzed. Thermodynamic analysis showed that the proposed thermochemical multilevel sorption thermal battery has the potential capacity for meeting the challenge of solar heat storage during the random variation of low and high solar insolation with time by using cascaded thermal energy storage technology. An energy density higher than 1200 kJ/kg of reactant can be attained from the advanced energy storage system. The promising method can enhance the versatility and working reliability of solar heat storage due to its distinct advantages of high energy density and a wide range of solar collection temperature when compared with conventional heat storage methods. It has potential applications for energy management of renewable energy utilization and waste heat recovery in large-scale industrial processes.